PEMBUATAN PROGRAM HITUNG PRODUKSI MENGGUNAKAN BAHASA PEMOGRAMAN VISUAL BASIC .NET UNTUK MENGEVALUASI PRODUKTIVITAS ALAT MUAT DAN ALAT ANGKUT PADA KEGIATAN PENAMBANGAN BATU GAMPING PT. SEMEN PADANG - Ikhwan Idham; Sumarya Sumarya; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2018)
Increased in cement demand for development has made PT. Semen Padang increased its cement production. Increased cement demand means increased demand for limestone as a base material for manufacturing cement. Based on data from PT. Semen Padang, the limestone mining production target in August 2016 was 718,000 tons, while the realization of the production 580,000 tons or about 81% of the production target. To determine the productivity of the loading and hauling equipment it is necessary to do some calculation phases. Up to this time, if the process of calculating the productivity of the equipement is done manually, it will take a long time and less practical. And it is expected that a program that can help with the productivity calculation process.Production calculation program is programmed using visual basic programming language. This program can be used to calculate the productivity of loading and hauling equipment. After the analysis and calculation done with the program, improving the productivity of the equipment must be done. To improve the productivity of the equipment, an improvement in the work efficiency of the equipment and the bucket fill factor excavator was made.Calculation results using the program, for the productivity of the loading equipment after the improvement the productivity of dump truck Komatsu HD 785 with Hitachi EX 2500-6 excavator is 721,179.27 tons /month. The calculation results using the program with the manual is not much different. The difference result of the calculation is caused by integrating the numbers behind the comma